Properties of the Picker Patient Experience questionnaire in a randomized controlled trial of long versus short form survey instruments. - Jenkinson, C; Coulter, A; Reeves, R; Bruster, S; Richards, N (2003)
BACKGROUND: The purpose of this study was to compare the performance of the 15-item Picker Patient Experience questionnaire (PPE-15) when embedded in a short form instrument as compared with a longer form measure. METHODS: A postal questionnaire survey of patients recently discharged from two hospital trusts was carried out. Patients were randomized to receive the PPE-15 in either a four-page or a 12-page survey instrument. RESULTS: A total of 1445 questionnaires were mailed to patients in either four- or 12-page formats. A total of 949 (65.67 per cent) forms were returned. No difference in response rate was found between the two versions of the questionnaire. Item completion and psychometric properties of the PPE-15 were not found to differ significantly between the two arms of the trial. CONCLUSION: In this survey the length of questionnaire in which the PPE-15 was embedded had no impact in terms of response rate or data quality. Consequently, the results suggest that length of questionnaire, up to the 108 items included in the 12-page survey, is unlikely to adversely affect results on the PPE-15.